(untitled) (Research, Society and Development, 2022)
Chronic Kidney Disease (CKD) is a disease that causes gradual and irreversible loss of kidney function and requires complex and expensive treatment. In recent years, CKD cases have increased significantly, which directly affects the SUS (Unified Health System). The study seeks support in the object, care in patients/clients with CKD. Thus, some guiding questions emerged: What care for people with CKD would be offered. Would these be effective? General objective: To understand the state of the art of studies on care for the subject with chronic kidney disease. Specific objectives: To identify studies on chronic kidney disease; establish thematic categories based on the findings; propose a product intended for care for people with chronic kidney disease. This is an integrative literature review, with application of the PICo and content analysis. Results: quantitative; production per year and types of methods used. Qualitative: Category 01-Scenario versus nursing care in the context of CKD. In this Category 02- Support network for patients/clients undergoing dialysis treatment. Category 03-Complications related to CKD. Conclusion: Therefore, it was observed that the patient/client with CKD has physical limitations to perform daily activities, walk, because due to the difficulty in erythropoietin, he develops anemia and the fatigue presented becomes inevitable, deficiency in performing physical efforts, carrying weight, among others, generating feelings of anguish/sadness due to the adaptations and changes generated, these changes happen as the CKD gets worse.